Fatigue properties of carbon fibre nano-composites - Lee, Jin Sheng. (2013)
Composites are getting more popular in the aerospace industry over the past decades. In recent years, researches on nano-composites are getting increasing attentions. Addition of nanoparticles was found to be able to improve the properties of composites.